Untargeted metabolomics analysis of glycerophospholipid metabolism in very low birth weight infants administered multiple oil lipid emulsions - Xiaoyan Zeng; Tao Yu; Luping Xia; Zhiqiang Ruan (BMC Pediatrics)
Abstract Background To compare the impact of two different lipid emulsions, specifically a soybean oil-based emulsion and a multiple oil emulsion (soybean oil, medium-chain triglycerides, olive oil, and fish oil, SMOF), on serum metabolites of very low birth weight (VLBW) infants using untargeted metabolomics analysis. Methods A comparative study was conducted on 25 VLBW infants hospitalized in neonatal intensive care units (NICU) of Hangzhou Women’s Hospital in 2023. The infants were divided into the SMOF group (13 cases) and the soybean oil group (12 cases) based on the type of lipid emulsion used during parenteral nutrition. Serum samples were collected at birth and 14 days later from both groups. An untargeted metabolomics analysis was conducted on serum samples using Ultra-high Performance Liquid Chromatography - Tandem Mass Spectrometry (UHPLC-MS/MS). Differential metabolites were identified using Orthogonal Partial Least Squares Discriminant Analysis (OPLS-DA) modeling, with criteria of variable importance in the projection (VIP) > 1 and false discovery rate (FDR) < 0.05. Functional annotation of the top 30 differential metabolites, ranked by VIP value, was conducted using the Kyoto Encyclopedia of Genes and Genomes (KEGG) database. Subsequently, enrichment and topological analyses were conducted with MetaboAnalyst software to identify key metabolic pathways. Finally, receiver operating characteristic (ROC) analysis was performed on metabolites associated with the identified key metabolic pathways. Results The metabolomic analysis revealed that, in the OPLS-DA model, no significant metabolite differences were found in umbilical cord blood between the two groups. However, 84 differential metabolites were identified in the 14-day samples from the SMOF group compared to the soybean oil group. According to MetaboAnalyst analysis, glycerophospholipid metabolism emerged as the most significantly altered metabolic pathway following the administration of SMOF lipid emulsion. Additionally, ROC curve analysis confirmed a significant increase in LysoPC(20:5), PE(16:0/20:5), and PE-NMe(22:5/16:0) metabolites in the SMOF group. Conclusion The administration of SMOF lipid emulsion in VLBW infants resulted in significant modifications of serum metabolites compared to traditional soybean oil-based lipid emulsions. Notably, glycerophospholipid metabolism was identified as the most prominently altered metabolic pathway. Metabolites, including LysoPC(20:5), PE(16:0/20:5), and PE-NMe(22:5/16:0), emerged as potential biomarkers. Clinical trial number Not applicable.